“Bygone Days” And Lessons Of The Past - I. M. Juraev; H. A. Juraev (Zien Journals, 2022)
In the article, based on the life and work of Abdulla Qadiri, the interrelated and harmonious aspects of the family environment, personality decline, and social-spiritual life crises are analyzed
Keywords: Historical reality; personal education; domestic life; family environment